Rapid and Affordable High Throughput Screening of SARS-CoV-2 Variants Using Denaturing High-Performance Liquid Chromatography Analysis - Turba, Maria Elena; Mion, Domenico; Papadimitriou, Stavros; Taddei, Francesca; Dirani, Giorgio; Sambri, Vittorio; Gentilini, Fabio (Frontiers in Virology, 2022)
Mutations in the receptor binding domain (RBD) region of SARS-CoV-2 have been shown to impact the infectivity, pathogenicity, and transmissibility of new variants of concern (VOCs). In addition, those mutations have the potential of causing immune escape, undermining the population immunity induced by ongoing mass vaccination programs. There is an urgent need for novel strategies and techniques aimed at the surveillance of the active emergence and spread of the VOCs. The aim of this study was to provide a quick, cheap and straightforward Denaturing High-Performance Liquid Chromatography (DHPLC) method for the prompt identification of the SARS-CoV-2 VOC. Two PCRs were designed to target the RBD region, spanning residues N417 through N501 of the Spike protein. Furthermore, a DHPLC screening analysis was set up. The screening consisted of mixing the unknown sample with a standard sample of a known variant, denaturing at high temperature, renaturing at room temperature followed by a 2-minute run using the WAVE DHPLC system to detect the heteroduplexes which invariably originate whenever the unknown sample has a nucleotide difference with respect to the standard used. The workflow was able to readily detect all the variants including B.1.1.7, P.1, B.1.585 B.1. 617.2 and lineages at a very affordable cost. The DHPLC analysis was robust being able to identify variants, even in the case of samples with very unbalanced target concentrations including those samples at the limit of detection. This approach has the potential of greatly expediting surveillance of the SARS-CoV-2 variants.